Examining Specific Theory-of-Mind Aspects in Amnestic and Non-Amnestic Mild Cognitive Impairment: Their Relationships with Sleep Duration and Cognitive Planning - Areti Batzikosta; Despina Moraitou; Paschalis Steiropoulos; Georgia Papantoniou; Georgios A. Kougioumtzis; Ioanna-Giannoula Katsouri; Maria Sofologi; Magda Tsolaki (Brain Sciences)
Background/Objectives: The study examined the relationships between specific Theory-of-Mind (ToM) dimensions, cognitive planning, and sleep duration in aging adults. Methods: The sample included 179 participants, comprising 46 cognitively healthy individuals, 75 diagnosed with amnestic Mild Cognitive Impairment (aMCI), and 58 with non-amnestic (naMCI). The mean age of the participants was 70.23 years (SD = 4.74), with a mean educational attainment of 12.35 years (SD = 3.22) and gender distribution of 53 men and 126 women. ToM assessment included tasks measuring the understanding and interpretation of non-literal speech, proverbs and metaphors, as well as an emotion-recognition test. For cognitive planning, a Tower Test was utilized. Sleep duration was measured using actigraphy. Results: We identified significant differences in various ToM tasks’ performance between the groups, particularly in non-literal speech tasks and third-order ToM stories. The HC group consistently outperformed both MCI groups in these tasks, with aMCI showing higher performance than naMCI. Mediation analysis applied to examine potential direct and indirect effects of sleep duration on ToM tasks indicated that total sleep time had significant indirect effects through cognitive planning—mainly as rule violation total score—on specific ToM aspects. Hence, besides the effects of MCI pathologies and especially of naMCI, sleep duration seems also to be associated with ToM performance in aging via specific executive functioning decrements. Conclusions: The findings underscore the social implications of ToM deficits due to MCI and/or sleep duration decrease, particularly in naMCI older adults, as they can seriously impair their social interactions. Targeted interventions could improve emotional understanding, communication, and overall quality of life.